Dynamic Fuzzy Model to Detect Verbal Violence in Real Time - Campos, Obed; Pancardo Garcia, Pablo; Hernandez Nolasco, Jose Adan (Computer Science, 2022)
The crime rates in Mexico have been increasing in recent years, every day there are news on social media and in the news where assaults and verbal aggressions by criminals can be seen. Public transportation units suffer from violence that authorities have not been able to reduce, despite their efforts. That is why we have developed a fuzzy logic model that can adapt to almost any scenario thanks to the dynamism that we have implemented in each one of its stages. We have obtained promising results that we believe will be of great help to the authorities in the police headquarters to detect in real time the exact moment in which a verbal aggression typical of a violent assault is happening. This is a tool to help the authorities, not a substitution; making use of the latest technologies available to us.